Coupled magnetothermal effects in biomagnetic fluid flow over a stretched sheet with copper nanoparticles - Zainal, Nurul Amira; Zuberi, Haris Alam (Scipedia S.L., 2025)
The study of biomagnetic nanofluids has gained significant attention due to their applications in biomedical engineering and thermal management systems, where precise control of heat and fluid flow is crucial. This research investigates the coupled effects of a magnetic dipole, thermal radiation, and copper nanoparticles on biomagnetic nanofluid flow over a stretching sheet to analyze their impact on velocity and temperature distribution. The governing equations are solved numerically using MATLAB’s bvp4c solver over the computational domain [0, 20], and results are validated against benchmark studies to ensure accuracy. Findings reveal that increasing nanoparticle volume fraction enhances thermal conductivity but reduces velocity due to increased viscosity, while stronger ferromagnetic interactions intensify localized heating, significantly altering temperature gradients. Additionally, streamline analysis illustrates the magnetic field’s influence on flow structures, and surface plots provide a comprehensive visualization of heat dissipation within the nanofluid. The study also highlights the role of viscous dissipation and Prandtl number in thermal regulation, offering insights applicable to magnetic hyperthermia treatments, targeted drug delivery, and advanced cooling technologies.